Contents and Foreword for the ATIKAN Journal, issue of December 2013 - ATIKAN, Editor Journal (ASPENSI, 2013)
This journal, with ISSN 2088-1290, was firstly published on June 1, 2011. Since June 2012 edition, it has been organized by the Faculty of Education and Teacher Training UNSUR (University of Suryakancana) in Cianjur, West Java, Indonesia and published by Minda Masagi Press as one of the publishers owned by ASPENSI (Association of Indonesian Scholars of History Education) in Bandung. The ATIKAN journal is published twice a year i.e. every June and December.Â Â Prof. Dr. H. Dwidja Priyatno Honorable Patron of the ATIKAN Journal in Bandung; and Rector of UNSUR (Suryakancana University) in Cianjur, West Java, Indonesia